Nürnberger Fastnachtspiele des 15. Jahrhunderts von Hans Folz und seinem Umkreis : Edition und Kommentar - Biehl, Theresia; Gerhardt, Christoph; Greil, Stefan Hannes; Przybilski, Martin; Ritz, Mark (De Gruyter, 2020)
For the first time, this edition provides a modern reproduction of the Shrovetide plays ascribed to Hanz Folz and his circle, one that meets the demands of scholarship and diplomtics. Final commentaries examine issues of authorship and place the thematic content in its literary-historical context. The text commentaries offer assistance with translation and help make the texts accessible for teaching.